Estudo da influência da adição de arame frio no processo de soldagem ao arco submerso com dois arames energizados: aspectos operacionais e metalúrgicos - Moara Marques de Castro (2017)
Submerged arc welding is a mechanized and highly productive process usually applied in the fabrication of large metallic structures. In order to meet actual industry demand to enhance productivity, modifications on its conventional operation are being developed. This investigation aims to study one of these modifications, which allows an increase in the deposition rate without increasing energy consumption through the introduction of a cold wire (not energized) between two hot wires, connected to one power source. This configuration was used in the welding of carbon steel plates, with current from 700 to 900 A and the ratio of the feed speed of the cold and hot wires varying from 0 to 1. The tests were conducted aiming to evaluate the influence of the addition of the cold wire on the morphology of the bead, on the metallurgical characteristics of the weld and on the operability of the process. The electrical signals of the experimental tests were monitored to analyze the stability of the process as the cold wire amount increased. The weld beads were characterized by hardness testing and metallography of the unchanged base metal (which had its chemical composition verified) up to the fusion zone. Microstructures were analyzed in order to estimate the thermal cycle of the weld. A theoretical model of the heat flux based on the Rosenthal equations was adapted to the experimental conditions of this study, in order to estimate the thermal effect of cold wire addition in the process. The experimental results suggest that this addition leads to a decrease in the temperature of the fusion zone because the cold wire acts as a heat sink during the welding procedure. Nevertheless, the energy absorbed by the cold wire that returns to the system is not considered in the current study, and thereby, its affect is overestimated. The results review that the addition of a cold wire produces welds with greater reinforcements and lower dilution, without changing the penetration or bead width. Furthermore, the heat input is kept unchanged for the tested configuration and accordingly the introduction of cold wire between the energized ones reduces their feeding speed, indicating that it may possibly influence arcs melting efficiency.